Gambaran Kadar Kreatinin Serum Pada Peminum Kopi di Desa Cikuya Kecamatan Banjarharjo Kabupaten Brebes Jawa Tengah - Umi Nihayatul Khusna; Anwar Jaman; Dwi Yuliani; Sofia Nuraeni; Nur Setyaningsih (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
One of the most important organs in the body and has an important role in maintaining body health is the kidneys. Caffeine as one of the factors causing chronic kidney failure is found in coffee drinks. Coffee contains caffeine compounds which can have a negative impact on the kidneys because they can cause caffeine to accumulate in the kidney glomeruli, which causes creatinine levels to increase and kidney function to decrease. The aim of this research was to determine the results of checking creatinine levels in coffee drinkers in Cikuya Village, Banjarharjo District, Brebes Regency, Central Java. This research is descriptive in nature. The sample in this study was 40 coffee drinkers in Cikuya Village, Banjarharjo District, Brebes Regency, Central Java. Based on the research results, results were obtained from the 40 samples studied, namely: with high creatinine levels in 7 samples (17.5%), normal creatinine levels in 29 samples (72.5%), and low creatinine levels in 4 samples (10%). These results show that the average creatinine level in male coffee drinkers in Cikuya Village, Banjarharjo District, Brebes Regency, Central Java, has normal creatinine levels in accordance with the normal value for creatinine examination, namely 0.7 mg/dl – 1.3 mg/dl.